EFEKTIVITAS METODE AL-MIFTAH LIL ʻULUM DALAM MENINGKATKAN KUALITAS MEMBACA KITAB KUNING PADA SANTRI MADRASAH DINIAH - Ibnu Ubaidillah; Ali Rif’an (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
This study uses a qualitative descriptive method with a case study approach. Data collection techniques use the method of interview, observation, and documenta-tion. Data analysis is done by condensing data, then presenting data, and conclusions drawn from the data. In checking the validity of the data, researchers use methods, namely extending the time of partici-pation of researchers in the field, increasing persistence of observation, using appropriate reference materials, and reading book tests. The results of the analysis show that the process of applying the Al-Miftah Lil ‘Ulum Method at Madin Wustho Hidayatul Mubtadi’in –Malang City was carried out through several stages, namely preparation, implementation, and evaluation. Among the supporting factors of the learning process and the inhibiting factors to applied it.